A numerical tool in MATLAB used to adapt three-dimensional conceptual models from ArcMap to TOUGH3. (December 2021) - Aguilar-Ojeda, José Alonso; Campos-Gaytán, José Rubén; Villela-Y-Mendoza, Almendra; Herrera-Oliva, Claudia Soledad; Ramírez-Hernández, Jorge; Kretzschmar, Thomas Gunter
Abstract: TOUGH3 is a powerful numerical tool that simulates the heat and fluid flows in porous and fractured media. However, setting up the "MESH" file for a model with several rock types is tedious and error-prone. This study presents a MATLAB code for converting ArcMap three-dimensional conceptual models into TOUGH3 input files. This code builds a rectangular computational mesh using the MESHMAKER tool and a text file containing the ArcMap geological model information. The MESHMAKER tool performs the discretization of the model and generates the coordinates. The code reads the coordinates and rock types file to rewrite a "MESH" file with the correct assignment of the various rock types required to build the model for TOUGH3. The modular structure of this code provides a useful framework for rewriting "MESH". The versatility and capabilities of the MATLAB code developed herein are demonstrated on a complex conceptual model of the Los Humeros geothermal reservoir in Puebla, Mexico. Highlights: The manuscrip describes an original algorithm developed in the program language MATLAB. The algorithm automatically allows to adapt 3D models developed in ArcMap to the modelling program TOUGH3. The algorithm builds a mesh and re-writing the MESH file with the rock-layers types wanted to include in the model. To test the performance applies the program to the conceptual model of one actual geothermal field in Mexico.